(untitled) (Journal of the College of Basic Education, 2022)
The political advertisement has become a major variable that cannot be overlooked or ignored in the political process, especially in the periods of elections or political events, in which competition is witnessed between candidates representing different currents and tendencies, and they use the minds of the masses as an arena for the fierce struggle between them in order to achieve certain goals and objectives of his decree, and therefore Studies of political advertising have appeared, which varied in aspects of their methods for this variable, and differed in the ways in which they display its impact, techniques, and methods. Thus, political advertisements become a distinct intellectual process for defining political candidates. They try, through their multi-purpose contents, to reflect the image of the electoral politics of the candidates comprehensively and effectively. publicly.